2001
DOI: 10.1111/j.1745-4530.2001.tb00547.x
|View full text |Cite
|
Sign up to set email alerts
|

DIFFUSION OF BEET DYE DURING ELECTRICAL AND CONVENTIONAL HEATING AT STEADY‐STATE TEMPERATURE1

Abstract: Ohmic heating has been shown to alter mass transfer properties of fruit and vegetable tissue. Diffusion of beet dye from beetroot tissue into a fluid was studied during conventional and ohmic heating as a function of steady‐state temperature. The volume of beet dye diffusing into solution during ohmic heating was enhanced with respect to conventional heating at 42C and 58C, but not at 72C. This can be explained by examining the differences in electrical conductivity of beet tissue at these temperatures during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(13 citation statements)
references
References 7 publications
0
12
0
1
Order By: Relevance
“…However, the effects of OH are not purely thermal. Several researches have noted that OH also induces electropermeabilization [48,51,52,65,76,86]. It was shown that even mild OH electrical treatments permitted enhanced diffusion in vegetable tissues [53].…”
Section: Principles Of Oh Treatmentmentioning
confidence: 98%
“…However, the effects of OH are not purely thermal. Several researches have noted that OH also induces electropermeabilization [48,51,52,65,76,86]. It was shown that even mild OH electrical treatments permitted enhanced diffusion in vegetable tissues [53].…”
Section: Principles Of Oh Treatmentmentioning
confidence: 98%
“…Scanning electronic microscopy (SEM) and X-ray diffraction (XRD) are frequently used to characterize edible films' structure [5,50]. SEM may be used to evaluate film homogeneity, layer structure, pores and cracks, surface smoothness and thickness, while XRD is mainly used to evaluate the degree of crystallinity of the films.…”
Section: Structure Characterizationmentioning
confidence: 99%
“…Diffusion is enhanced, electrical conductivity changes are more linear during heating, and moisture migrates more easily out of the tissue (Halden, de Alwis, & Fryer, 1990;Imai, Uemura, Ishida, Yoshizaki, & Noguchi, 1995;Lima, Heskitt, & Sastry, 2001;Schreier, Reid, & Fryer., 1993). Thus, ohmic pretreatment has been found useful in drying and juice extraction processes (Wang & Sastry, 1998), and in sugar extraction from beets (Fedorenchenko et al, 1983).…”
Section: Introductionmentioning
confidence: 96%